Autopsy What Do We Learn from Corpses? - Hakan Dogan, Kamil (IntechOpen, 2022)
If a death is suspicious, an autopsy of the body is performed with the intent of determining the cause and manner of death. A death investigation begins with body examination and evidence collection at the scene and proceeds through history, postmortem examination and autopsy, laboratory tests, and determining the cause and manner of death. This book provides a comprehensive overview of postmortem examination and autopsy, the steps involved, and what the results of the examination can tell us.